2022
DOI: 10.31234/osf.io/xdbf9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When Group Members Dissent: A Direct Comparison of the Black Sheep and Intergroup Sensitivity Effects

Abstract: How do people react to opinion conflict occurring within an ingroup? Whereas some work suggests that dissenting ingroup members evoke more negativity than equivalently dissenting outgroup members (termed the black sheep effect), other research instead finds that people are more receptive to dissent from within the group relative to the same opinion originating from outsiders (termed the intergroup sensitivity effect). We sought to integrate these largely independent lines of work by investigating how people re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…Table 1). This finding runs counter to the large uninvolved bystander effects observed in the two registered reports and prior observations of involved bystander ISEs (Adelman & Verkuyten, 2020), though evidence for the latter is mixed (Reiman & Killoran, 2023). It is possible that agreement with the criticism reduces the ISE, much like neutral or positive comments do (Hornsey et al., 2002; Thürmer & McCrea, 2018).…”
Section: Beyond Punishment: Response Target and Valencecontrasting
confidence: 95%
See 1 more Smart Citation
“…Table 1). This finding runs counter to the large uninvolved bystander effects observed in the two registered reports and prior observations of involved bystander ISEs (Adelman & Verkuyten, 2020), though evidence for the latter is mixed (Reiman & Killoran, 2023). It is possible that agreement with the criticism reduces the ISE, much like neutral or positive comments do (Hornsey et al., 2002; Thürmer & McCrea, 2018).…”
Section: Beyond Punishment: Response Target and Valencecontrasting
confidence: 95%
“…Indeed, participants reported that intergroup‐criticism was less appropriate (counter‐normative) than was intragroup criticism (Sutton et al., 2006). Furthermore, Adelman and Verkuyten (2020) recently found that individuals were more willing to tolerate intragroup criticism than intergroup criticism, even when the source was a member of the participant's ingroup (but see Reiman & Killoran, 2023). Participants thus even rejected critical comments about another group when the commenter was a member of their own group (i.e., involved bystander ISE , Table 1).…”
Section: The Intergroup Sensitivity Effectmentioning
confidence: 99%